Cold forging steel
Optimizing the steel composition with Cr and C promotes uniform carbide dispersion, addressing uneven cementite distribution issues in hypoeutectoid steel, enhancing cold forging performance and preventing cracking.
Patent Information
- Application Number
- JP2021043867
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-17
- Publication Date
- 2025-02-10
- Estimated Expiration
- 2041-03-17
AI Technical Summary
The uneven distribution of spheroidized cementite in the two-phase structure of hypoeutectoid steel during spheroidizing annealing leads to non-uniform deformation and cracking during cold forging, which compromises the workability of the material.
The steel composition is optimized with specific components like Cr, C, and other additives to promote uniform dispersion of spheroidized carbides by enhancing C diffusion from pearlite and bainite grains to ferrite grains, ensuring stable precipitation of mixed Fe-Cr carbides during austenitization.
The resulting steel exhibits uniform carbide distribution, reducing the likelihood of cracking during cold forging, with improved cold forging properties and hardness below 83HRB, enabling high-compression cold forging without defects.
Smart Images

Figure 0007628445000005 
Figure 0007628445000006 
Figure 0007628445000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a hypoeutectoid steel for cold forging, and in particular to a steel that has excellent cold forgeability when cold forging is used for forming parts, due to the uniform dispersion of spheroidized carbides throughout the steel as a result of spheroidizing annealing. [Background technology]
[0002] When hypoeutectoid steel, which is a low carbon steel, is processed to form parts, cold forging is sometimes selected from the viewpoint of improving yield and production efficiency. In addition, when cold forging is performed, spheroidizing annealing is usually performed to reduce deformation resistance.
[0003] The spheroidizing annealing of hypo-eutectoid steel usually involves the following steps: (Step 1) Raise the temperature to the A1 point or higher. (Step 2) Hold the temperature at or above the A1 point to create a structure consisting of two phases, ferrite and austenite. (Step 3) After that, slowly cool from just above the A1 point to just below the A1 point in order to suppress the austenite to pearlite transformation. At this time, spheroidal cementite precipitates at the austenite / ferrite interface of the two-phase structure, and after slow cooling to just below the A1 point is completed, a structure is formed in which spheroidal cementite precipitates within the ferrite grains.
[0004] In the spheroidized annealed structure of hypo-eutectoid steel, uneven distribution of spheroidized cementite after slow cooling may occur due to the process of holding the structure in the two-phase region consisting of the ferrite phase and the austenite phase in (Step 2). Such uneven distribution of cementite is undesirable from the viewpoint of workability because it promotes uneven deformation during cold forging and is one of the causes of cracking.
[0005] In conventional steel materials with excellent cold forgeability, for example, case-hardened steel materials have been proposed that aim to improve cold forgeability by appropriately controlling the area ratios of ferrite, bainite, and pearlite before spheroidizing annealing to balance the shape, density, and dispersion state of spheroidized carbides after spheroidizing annealing (see Patent Document 1).
[0006] In addition, a steel wire rod or bar for case hardening has been proposed in which fine carbides caused by bainite are dispersed after spheroidizing annealing by ensuring an appropriate bainite area ratio before spheroidizing annealing, thereby improving cracking (see Patent Document 2).
[0007] In addition, a case-hardened steel for cold forging has been proposed in which, in a structure consisting of two phases, ferrite and pearlite, before spheroidizing annealing, the ferrite grains and pearlite grains are made smaller to increase the ferrite / pearlite grain boundaries and promote cementite precipitation at the interfaces, thereby shortening the spheroidizing annealing time and uniformly dispersing cementite, thereby ensuring cold forgeability (see Patent Document 3). [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2014-185389 A [Patent Document 2] JP 2005-220377 A [Patent Document 3] Japanese Patent Application Publication No. 11-012684 Summary of the Invention [Problem to be solved by the invention]
[0009] In the spheroidized annealed structure of hypo-eutectoid steel, uneven distribution of spheroidized cementite after slow cooling may occur due to the above-mentioned (Step 2) step of maintaining the structure in the two-phase region consisting of the ferrite phase and the austenite phase. Since such uneven distribution of cementite promotes uneven deformation during cold forging and is one of the causes of cracking, it is desirable to make the distribution of cementite uniform from the viewpoint of workability.
[0010] Although the above-mentioned proposals in the prior art attempt to optimize the shape and dispersion state of spheroidized cementite after spheroidizing annealing, all of them are merely proposals to appropriately control the structure before spheroidizing annealing. In other words, when looking at the inside of ferrite grains in the two-phase structure consisting of the ferrite phase and the austenite phase in (step 2) in the normal spheroidizing annealing process, spheroidized cementite cannot be precipitated, and therefore it cannot be said that they adequately deal with the prevention of non-uniform distribution of spheroidized cementite.
[0011] Therefore, the problem to be solved by the present invention is to provide a steel capable of suppressing cracking during cold forging by uniformly dispersing spheroidized carbides throughout the structure. [Means for solving the problem]
[0012] The inventors of the present application have conducted extensive research focusing on the C diffusion behavior just below the austenitizing temperature. In conventional hypoeutectoid steels, solute C in ferrite grains stably precipitates as M3C carbides (cementite) just below the austenitizing temperature. Therefore, C exists as M3C carbides in both pearlite grains (structures composed of ferrite and lamellar cementite) and bainite grains (structures composed of ferrite and cementite) and ferrite grains (cementite is stably precipitated). As a result, it is difficult to create a difference in C diffusion behavior, and sufficient driving force for C diffusion from pearlite grains and bainite grains to ferrite grains cannot be obtained.
[0013] On the other hand, by using a high Cr content, the solute C in the ferrite grains stably precipitates as M7C3 type (M = Fe and Cr mixed components) carbides just below the austenitization temperature. In other words, the difference in C diffusion behavior between pearlite grains (structures composed of ferrite and lamellar cementite) and bainite grains (structures composed of ferrite and cementite) and ferrite grains (M7C3 carbides are stable) becomes large. As a result, it was found that the C diffusion from pearlite grains and bainite grains to ferrite grains is sufficiently promoted.
[0014] Therefore, by adjusting the composition of the steel, it was discovered that the stable carbides within the ferrite grains just below the austenitization temperature were made to be of the M7C3 type, which made it easier to uniformly disperse spheroidized carbides.
[0015] In this way, the inventors of the present application have discovered that by subjecting steel having a specified chemical composition to a specified spheroidizing annealing, spheroidized carbides are uniformly dispersed throughout the structure, resulting in a steel that can suppress cracking during cold forging.
[0016] Then, when the structure before heat treatment is a two-phase structure of ferrite and pearlite, a two-phase structure of ferrite and bainite, or a three-phase structure of ferrite, pearlite, and bainite, (a) during holding just below the austenitizing temperature, the lamellar cementite that constitutes pearlite and the cementite that constitutes bainite dissolve and spheroidize, (b) solute C flows into the ferrite grains, (c) M7C3 type carbides precipitate in the ferrite grains, and (d) these grow into spheroidized carbides, resulting in a steel with spheroidized carbides uniformly dispersed throughout. Here, the M7C3 type carbides are a mixture of M=Fe and Cr.
[0017] In view of the above, a first means for solving the problems of the present invention is a cold forging steel comprising, in mass%, 0.14-0.45% C, 0.05-1.00% Si, 0.10-0.90% Mn, 1.30-3.50% Cr, 0.020-0.200% Al, 0.0040-0.0300% N, the balance being Fe and unavoidable impurities, in which the unavoidable impurities are P: 0.030% or less and S: 0.030% or less, and which has an A1 point of 750°C or more and has M7C3 type carbides (wherein M in the M7C3 type carbides is Fe or Cr).
[0018] The second means is a cold forging steel which contains, in addition to the chemical components described in the first means, one or more of Ni: 0.02-2.00% and Mo: 0.02-2.00%, with the balance being Fe and unavoidable impurities, in which the unavoidable impurities are P: 0.030% or less and S: 0.030% or less, has an A1 point of 750°C or more, and has M7C3 type carbides (wherein M in the M7C3 type carbides is Fe or Cr).
[0019] The third means is a cold forging steel containing, in addition to the chemical components described in the first or second means, one or more of Nb: 0.02-0.10%, Ti: 0.020-0.200%, B: 0.0010-0.0050%, and V: 0.010-0.500%, with the balance being Fe and unavoidable impurities, in which P and S as the unavoidable impurities are P: 0.030% or less and S: 0.030% or less, and which has an A1 point of 750°C or more and M7C3 type carbides (wherein M in the M7C3 type carbides is Fe or Cr). Effect of the Invention
[0020] In the cold forging steel of the present invention, M7C3 carbides are precipitated in the prior ferrite grains, and thus the spheroidized carbides are uniformly dispersed throughout the structure. In addition, the area ratio of the ferrite grains in which the spheroidized carbides are not precipitated is within 6.0% of the entire structure, and the area ratio of the remaining pearlite grains and bainite grains after spheroidizing annealing is also 5.0% or less, so that the spheroidization of the carbides is sufficiently advanced. As a result, the steel does not crack even under high compression by cold forging. Thus, the cold forging steel of the present invention has a hardness of 83HRB or less, and can be cold worked without cracking even when cold forged at a cold upsetting rate of 75%, and thus the cold forging steel of the present invention exhibits excellent cold forgeability. [Brief description of the drawings]
[0021] [Figure 1] FIG. 2 is a schematic diagram for explaining the temperature history of the holding temperature T (° C.), holding time (hr), and air cooling in the spheroidizing annealing conditions. [Diagram 2]The optical microscope photographs, the area ratio of ferrite grains without spheroidized carbide precipitation, and the area ratio of remaining pearlite and bainite are shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Before describing the embodiment of the steel according to the present invention, the reasons for specifying the composition of the steel, the reasons for specifying the lower limit of the A1 point, and the reasons for having M7C3 type carbides will be described. Note that % in the following composition is mass %.
[0023] C: 0.14-0.45% C is an element that improves the hardness of the material. If the C content is less than 0.14%, the core hardness after carburization decreases, resulting in insufficient strength. On the other hand, if the C content exceeds 0.45%, the material hardness increases too much, reducing workability, resulting in poor machinability and cold forgeability. Therefore, the C content is set to 0.14 to 0.45%, and preferably 0.14 to 0.30%.
[0024] Silicon: 0.05 to 1.00% Silicon is a useful element for deoxidization. If the silicon content is less than 0.05%, there will be a shortage of deoxidizing material. On the other hand, if the silicon content exceeds 1.00%, the material hardness will increase too much, reducing workability, and carburization will be inhibited. Therefore, the Si content is set to 0.05 to 1.00%, and preferably, the Si content is set to 0.30 to 0.80%.
[0025] Mn: 0.10 to 0.90% Mn is an element that improves hardenability. If the Mn content is less than 0.10%, hardening will be insufficient. On the other hand, if the Mn content exceeds 0.90%, workability will decrease. Therefore, the Mn content is 0.10 to 0.90%, and preferably 0.15 to 0.50%.
[0026] Cr: 1.30~3.50% Cr is an element that stabilizes M7C3 type carbides. If Cr is less than 1.30%, M7C3 type carbides do not precipitate, so that the amount of C that flows from pearlite grains to ferrite grains during spheroidizing annealing is insufficient, and the distribution of spheroidized carbides becomes non-uniform, resulting in a decrease in cold forgeability. In addition, hardenability is insufficient. On the other hand, if Cr exceeds 3.50%, the material hardness increases too much, resulting in a decrease in workability. In addition, carburization inhibition occurs. Therefore, Cr is set to 1.30 to 3.50%. Desirably, Cr is set to 1.40 to 2.50%.
[0027] Al: 0.020~0.200% Al is an element useful for deoxidization. If Al is less than 0.020%, it will be insufficient as a deoxidizer. In addition, since there will be a shortage of fine nitrides, there will be a shortage of precipitation nuclei for M7C3 type carbides, and the toughness and fatigue properties will decrease due to the coarsening of crystal grains. On the other hand, if Al exceeds 0.200%, coarse nitrides will be formed, and the fatigue properties and workability will decrease. Therefore, Al is set to 0.020 to 0.200%. Desirably, Al is set to 0.020 to 0.050%.
[0028] N: 0.0040~0.0300% N is an element that forms nitrides. If N is less than 0.0040%, fine nitrides are insufficient, resulting in a shortage of precipitation nuclei for M7C3, and the toughness and fatigue properties are reduced due to the coarsening of crystal grains. On the other hand, if N exceeds 0.0300%, coarse carbonitrides are formed, resulting in a deterioration of fatigue properties and workability. Therefore, N is set to 0.0040 to 0.0300%. Desirably, N is set to 0.0040 to 0.0200%.
[0029] P: 0.030% or less as unavoidable impurities If the P content exceeds 0.030%, the toughness decreases due to grain boundary segregation, so even if P is contained as an unavoidable impurity, the content is set to 0.030% or less.
[0030] S: 0.030% or less as unavoidable impurities If the S content exceeds 0.030%, MnS is formed, which reduces the toughness and fatigue strength. Therefore, even if S is contained as an unavoidable impurity, the S content is set to 0.030% or less.
[0031] The following components describe optional ingredients that may be optionally added. Ni: 0.02 to 2.00% Ni is an element that improves hardenability and toughness. If Ni is less than 0.02%, the effect of improving hardenability is small, and the effect of improving toughness is also small. On the other hand, if Ni is added in an amount exceeding 2.00%, not only will the cost increase, but the material hardness will also increase, resulting in a decrease in workability. Therefore, when Ni is added, it is set to 0.02 to 2.00%. Desirably, the amount of Ni added is 0.02 to 1.80%.
[0032] Mo: 0.02 to 2.00% Mo is an element that improves hardenability. If Mo is less than 0.02%, the effect of improving hardenability is small. On the other hand, if Mo exceeds 2.00%, in addition to increasing costs, the material hardness also increases, resulting in reduced workability. Therefore, when Mo is added, it is set to 0.02 to 2.00%. Desirably, the amount of Mo added is 0.02 to 0.50%.
[0033] Nb: 0.02 to 0.10% Nb is an element that generates carbonitrides and suppresses grain coarsening. If the Nb content is less than 0.02%, the amount of fine carbonitrides is insufficient, so the effect of suppressing grain coarsening is reduced, and the toughness and fatigue strength are insufficient. On the other hand, if the Nb content exceeds 0.10%, the amount of carbonitrides becomes excessive and the workability is reduced. Therefore, when Nb is added, it is set to 0.02 to 0.10%. Desirably, the amount of Nb added is 0.02 to 0.08%.
[0034] Ti: 0.020~0.200% Ti is an element that generates carbonitrides and suppresses grain coarsening. If Ti is less than 0.020%, the amount of fine nitrides is insufficient. In addition, N is not fixed and forms BN, which reduces hardenability. In addition, the effect of suppressing grain coarsening is reduced. On the other hand, if the Ti content exceeds 0.200%, the amount of carbonitrides becomes excessive, resulting in a decrease in workability. Therefore, when Ti is added, the content is set to 0.020 to 0.200%, and preferably, the content of Ti added is set to 0.020 to 0.100%.
[0035] B: 0.0010~0.0050% B is an element that improves hardenability. If B is less than 0.0010%, the effect of improving hardenability is small. If B exceeds 0.0050%, the workability decreases due to an increase in material hardness. Therefore, when B is added, the content is set to 0.0010 to 0.0050%. Preferably, the amount of B added is 0.0010 to 0.0030%.
[0036] V: 0.010~0.500% V is an element that generates carbonitrides and suppresses grain coarsening. If V is less than 0.010%, fine carbonitrides are insufficient and the effect of suppressing grain coarsening is small, resulting in insufficient toughness and fatigue strength. On the other hand, if V exceeds 0.500%, the amount of carbonitrides becomes excessive and workability decreases. Therefore, when V is added, it is set to 0.010 to 0.500%. Desirably, V is added in an amount of 0.010 to 0.400%.
[0037] A1 point: 750℃ or higher If the A1 point is less than 750°C, the holding temperature for spheroidizing annealing will be low, and the spheroidization of the carbides that compose pearlite and bainite will be insufficient. As a result, the cold workability will decrease due to insufficient softening. Therefore, the A1 point is set to be 750° C. or higher. More preferably, the A1 point is set to be 750 to 800° C. In addition, A1 in the present invention can be calculated using Ac1 = 723°C-14Mn[%]+22Si[%]-14.4Ni[%]+23.3Cr[%].
[0038] The presence of M7C3 type carbides In the spheroidizing annealing, if the diffusion of carbon from pearlite grains and bainite grains to ferrite grains is insufficient, carbides cannot precipitate in the ferrite grains, resulting in non-uniform carbide distribution and reduced cold forgeability. Therefore, in the present invention, M7C3 type carbides are allowed to exist. This results in a large difference in the C diffusion behavior between pearlite grains (a structure composed of ferrite and lamellar cementite) and bainite grains (a structure composed of ferrite and cementite) on the one hand, and ferrite grains (in which M7C3 carbides are stable) on the other. As a result, C diffusion from the pearlite grains and bainite grains to the ferrite grains is sufficiently promoted, making it easier for the spheroidized carbides to disperse uniformly, resulting in excellent cold forgeability.
[0039] (Spheroidizing annealing conditions) 1 is a schematic diagram for explaining the holding temperature T (°C) and holding time t (hr) of the temperature history which are the spheroidizing annealing conditions. The holding temperature T and holding time t conditions for spheroidizing annealing in the present invention shall satisfy the following [Equations 1] to [Equations 3]. [Formula 1]: (A1 point -30℃)≦T≦(A1 point -5℃) [Formula 2]:t≧120 / (T-A1+50) [Formula 3]: A1=723℃-14Mn[%]+22Si[%]-14.4Ni[%]+23.3Cr[%]
[0040] (Manufacturing process of test material) Inventive steels No. 1 to 22 in [Table 1] and comparative steels No. 1 to 11 each having the chemical components described therein with the balance being Fe were melted in a 100 kg vacuum induction furnace (VIM) to produce steel ingots, which were then forged to φ32 at 1250°C, normalized at 925°C for 1 hour, and then cut to 100 mm to obtain test specimens.
[0041] [Table 1]
[0042] [Table 2]
[0043] (Spheroidizing annealing process) The test materials prepared above were subjected to spheroidizing annealing using a Kanthal furnace according to the following procedure: The test materials were placed in a furnace set to the holding temperature for spheroidizing annealing according to the holding temperature T and holding time t shown in Tables 3 and 4, the test materials were allowed to heat up for 30 minutes, and were held for the specified time, after which they were air-cooled.
[0044] [Table 3]
[0045] [Table 4]
[0046] (Check for the presence of M7C3 type carbides) For each of the spheroidized annealed test materials, TEM specimens were prepared from the D / 4 position using the extraction replica method, and the specimens were then observed using a transmission electron microscope (TEM).
[0047] (TEM observation conditions) For each test material sample, a total of 10 fields of view (10 μm × 10 μm) were photographed, and 5 carbides present in each field of view were randomly selected and subjected to identification analysis (component analysis by EDS, structural analysis by diffraction pattern) to confirm the presence or absence of M7C3 carbides. The results are shown in Tables 3 and 4.
[0048] (Measurement of the area ratio of ferrite grains where no spheroidized carbides are precipitated) After spheroidizing annealing, the test pieces were cut out from the D / 4 position, embedded in resin, polished, and the surface was etched with a nital etching solution. Five fields of view were then observed under an optical microscope at 400x magnification, and the area ratio was calculated by image analysis. In addition, when the number of spheroidal carbides having an equivalent circle diameter of 0.5 μm or more present in a ferrite grain is less than 5, the ferrite grain is defined as "a ferrite grain in which no spheroidal carbides are precipitated." As a result of measuring the area ratio of ferrite grains in which no spheroidized carbides were precipitated in the observation field after spheroidizing annealing, it can be said that those exceeding 6.0% of the whole structure are insufficiently spheroidized or not uniformly dispersed. The results are shown in Tables 3 and 4.
[0049] (Measurement of area ratio of remaining pearlite grains and bainite grains) Similarly, the test material after spheroidizing annealing was observed in five fields of view using an optical microscope at a magnification of 400 times, and calculations were made by image analysis. When the area ratio of the remaining pearlite grains and bainite grains after spheroidizing annealing is 5.0% or less, it can be said that the spheroidization of the carbides has progressed sufficiently, but when the area ratio of the remaining pearlite grains and bainite grains exceeds 5.0%, it can be said that the spheroidization of the carbides is insufficient, and the cold forgeability is reduced due to insufficient softening. The results are shown in Tables 3 and 4.
[0050] FIG. 2 shows optical microscope photographs of the inventive steel 6, the inventive steel 21, and the comparative steel 6 after spheroidizing annealing, as well as the area ratio of ferrite grains in which no spheroidized carbides were precipitated, and the area ratios of the remaining pearlite grains and bainite grains.
[0051] (Hardness measurement) The hardness of the spheroidized annealed steel bar material at the midpoint between the center and the outer circumference (called "D / 4" where D represents the diameter) was measured using a Rockwell hardness tester and taken as the hardness (HRB). If the spheroidized annealing hardness exceeds 83HRB, the cold forging deformability decreases, and cracks are likely to occur when cold forging is performed at a high processing rate. Therefore, it is desirable to set the spheroidized annealing hardness to 83HRB or less. The results are shown in Tables 3 and 4.
[0052] (Presence or absence of cracks when 75% cold upset) Cylindrical test pieces measuring φ14×21 mm were prepared from the center of the test material (the forging direction of the test material was parallel to the longitudinal direction of the test piece). Using these cylindrical test pieces, cold upsetting tests were carried out at room temperature. The upsetting speed was 10 mm / min, and the final upsetting rate (reduction rate of the height of the test piece) was 75%, and the test pieces were inspected for the presence or absence of surface cracks after processing. The results are shown in Tables 3 and 4.
[0053] The invention steels 1 to 22 are within the range of chemical composition defined by the present invention, and the A1 point is 750°C or higher. M7C3 carbides are confirmed in the spheroidized annealed grains. The area ratio of ferrite grains without precipitated spheroidized carbides is within 6.0% of the whole structure, and the area ratio of remaining pearlite grains and bainite grains is also within 5.0%, so that cold forged steels with sufficient spheroidization and uniform dispersion are obtained. In other words, the invention steels 1 to 22 all have a hardness of 83HRB or less, and did not show any cracks in a 75% cold upset test, so that the invention steels have excellent cold workability.
[0054] Comparative steels 1 and 2 contained excessive Mn and insufficient Cr, had an A1 point below 750°C, no M7C3 carbides were observed, and cracks were observed in the 75% cold upset test. Comparative steels 3 and 5 to 7 had an insufficient Cr content, the A1 point was below 750°C, no M7C3 carbides were observed, and cracks were observed in the 75% cold upset test. Comparative steel 4 had insufficient Cr and Al, the A1 point was below 750°C, no M7C3 carbides were observed, and cracks were observed in the 75% cold upset test. Comparative Example 8 had an excessive amount of Cr, was hard at 84 HRB, and cracks were observed in the 75% cold upset test. Comparative Example 9 contained excessive amounts of Mn and Cr, was hard at 85 HRB, and cracks were observed in the 75% cold upset test. Comparative Example 10 had an excessive amount of Si, was hard at 85 HRB, and cracks were observed in the 75% cold upset test. Comparative Example 11 had excessive amounts of C and Mo, was hard at 86 HRB, and cracks were observed in the 75% cold upset test.
Claims
1. In mass percent, C: 0.14-0.45%, Si: 0.05-1.00%, Mn: 0.10-0.90%, Cr: 1.30-3.50%, Al: 0.020-0.200%, N: 0.0040-0.0300%, The balance is Fe and unavoidable impurities. The P and S contents as inevitable impurities are P: 0.030% or less and S: 0.030% or less, A 1 The point is 750° C. or higher, M 7 C 3 Cold forging steel with die carbides. (However, M 7 C 3 M in the carbide type is Fe or Cr.
2. In addition to the chemical components described in claim 1, the alloy contains at least one of Ni: 0.02 to 2.00% and Mo: 0.02 to 2.00%, The balance is Fe and unavoidable impurities. The P and S contents as inevitable impurities are P: 0.030% or less and S: 0.030% or less, A 1 The point is 750° C. or higher, M 7 C 3 Cold forging steel with die carbides. (However, M 7 C 3 M in the carbide type is Fe or Cr.
3. In addition to the chemical components according to claim 1 or 2, Contains one or more of Nb: 0.02 to 0.10%, Ti: 0.020 to 0.200%, B: 0.0010 to 0.0050%, and V: 0.010 to 0.500%, The balance is Fe and unavoidable impurities. The P and S contents as inevitable impurities are P: 0.030% or less and S: 0.030% or less, A 1 The point is 750° C. or higher, M 7 C 3 Cold forging steel with die carbides. (However, M 7 C 3 M in the carbide type is Fe or Cr.
Citation Information
Patent Citations
Parts made of carburized steel excellent in pitting resistance
JP1994025823A
Case hardening steel for cold forging
JP1999012684A
Steel for highly facial pressure resistant member excellent in machinability and highly facial pressure resistant member
JP2001329336A
Steel wire rod or bar steel for case hardening having excellent cold forgeability after spheroidizing
JP2005220377A
Carburized component and manufacturing method thereof
JP2007308792A